Optimalisasi Potensi Pendederan dan Pembesaran Kerapu (Epinephelus sp.) berbasis Sumber Daya Alam di Desa Cangkring, Indramayu - Yani Hadiroseyani; Irzal Effendi; Tatag Budiardi; Iis Diatin; Apriana Vinasyiam; Kukuh Nirmala; Belinda Astari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Cangkring Village has various fishery resources, including ponds, fishponds, and access to waters that support fish farming. The Lecturer Returning Home Program aims to disseminate innovations in systems and appropriate technologies for integrated grouper fish farming through survey and training activities. This study used a survey method combined with a descriptive approach. Sampling was carried out using purposive sampling to collect data from fish farmers in Cangkring Village. The survey research was conducted to identify and analyze the potential for grouper (Epinephelus sp.) nursery and rearing based on natural resources in Cangkring Village, Indramayu. Field observations, questionnaires, and interviews were used to collect data. The recommended stocking density is around 32 fish/m3 for grouper fish rearing in KJT measuring 3×6×1 m for an initial weight of 100‒200 g, and 1,500‒2,000 fish/m3 for grouper seeds in KJT measuring 1.5×1.0×0.5 m to 2.5×1.25×0.8 m. Trash fish have great potential for the development of grouper fish breeding in tanks and ponds as well as rearing in floating net cages/floating net cages (KJT) in the estuary waters of the Cimanuk River, Cangkring Village. In addition, the coastal waters and estuaries of Cangkring Village are rich in rebon shrimp, with an abundance of around 900‒1800 fish/L. The larger the fish seeds, the lower the stocking density. This community empowerment activity is an alternative for the community to improve education and skills in fish farming which can later increase income through an integrated system of grouper nursery and rearing based on natural resources.